Simulation and analysis of suspension based single axis mems capacitive accelerometer - Veena S; Sthuti A; HL Suresh; Ashik s; Surya p; Nagaraj MJ (International Journal of Basic and Applied Science, 2022)
This paper reports a comparison of different types of springs used in MEMS based capacitive accelerometers. In this work MEMS based Single-axis accelerometers are designed using different Suspension systems. Analysis of the structure is done for resonant frequency of 2kHz. Analytical modeling of the different suspensions is presented for the specified frequency. Stress, displacement and capacitive analysis of the accelerometer is done. The sensitivity of the accelerometer with parallel beam  suspension is 70nm/g, 50nm/g for folded beam suspension and 35nm/g for serpentine beam suspension. Hence parallel beam suspension has 0.7 times improved sensitivity than folded beam and 2 times better than serpentine suspension accelerometer. Whereas the stress obtained for folded beam is better than the other two. Hence  Parallel beam suspension is preferred for higher sensitivity and accuracy whereas Folded beam suspension is preferred for greater structural stability By comparing these devices, it is concluded that a compromise on certain parameters is required in order meet the requirements. If there is higher displacement sensitivity then there is lower mechanical stability and vice versa. The simulations are carried out using COMSOL Multiphysics.